Analyzing the Influence of Promotion on Consumer Purchase Decisions Using a Binary Logistic Regression Model in Car Salon Services - Syauqi Ahtisya; Herdianto Herdianto; Diva Dinar Fasya; Jerry Heikal (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the influence of promotion on consumer purchasing decisions for car salon services using the binary logistic regression model. Promotion plays a crucial role in marketing strategy, particularly in service industries, as it helps build awareness and stimulates consumer decisions. Data were collected from 150 respondents who had been exposed to promotional activities conducted by car salon businesses. The independent variables examined in this research include promotion, price, brand switching, and prior experience, while the dependent variable is the consumer’s purchase decision. The data were analyzed using the binary logistic regression method with IBM SPSS 25 software. The results show that promotion and customer experience have a positive and significant effect on purchasing decisions, whereas price and brand switching have a significant negative effect. The final model achieved a classification accuracy of 74,0%, indicating that the selected variables can effectively explain consumer decision-making behavior. These findings highlight that effective promotional strategies and positive customer experiences significantly increase the likelihood of purchase, while high price perceptions and brand-switching tendencies reduce it. This study provides managerial implications for car salon service providers to enhance promotional effectiveness and improve customer satisfaction to foster long-term loyalty.